Barn Owl (Tyto alba) - Jason M. Martin; Richard N. Raid; Lyn C. Branch (EDIS)
Barn owls, members of the family Tytonidae, are unmistakable nocturnal birds of prey. Their ghostly appearance and blood-curdling shriek have led to their incorporation into folklore and myth and have earned these birds a variety of nicknames, including "ghost owl" and "monkey-faced owl." Thirty-six subspecies have been identified worldwide. The subspecies that lives in North America is called Tyto alba pratincola. This document is WEC 185, one of a series of the Department of Wildlife Ecology and Conservation, UF/IFAS Extension. Original publication date September 2005.